Answer:
3+2x
Step-by-step explanation:
Distribute the equation out.
1/4(12+8x)
(1/4*12)+(1/4*8x)
Multiple those out to get a new equation
3+2x
You cannot add those together because of the variable. Theres no way of knowing what x equals so this is as far as you can go therefor making the answer 3+2x
The answer to this equation is
x= 1, -3
Let x be the 1st odd number, and x+2 the second odd consecutive number:
(x)(x + 2) = 6[((x) + (x+2)] -1
x² + 2x = 6(2x + 2) - 1
x² + 2x = 12x +12 - 1
And x² - 10x - 11=0
Solve this quadratic expression:
x' = [+10 +√(10²- 4.(1)(-11)]/2 and x" = [+10 -√(10²- 4.(1)(-11)]/2
x' = [10 + √144]/2 and x" = [10 - √64]/2
x' = (10+12)/2 and x" = (10-12)/2
x = 11 and x = -1
We have 2 solutions that satisfy the problem:
1st for x = 11, the numbers at 11 and 13
2nd for x = - 1 , the numbers are -1 and +1
If you plug each one in the original equation :(x)(x + 2) = 6[((x) + (x+2)] -1
you will find that both generates an equlity
Asnwer:
15 Units
Hope this helps! :)